2016
DOI: 10.1186/s13071-016-1931-5
|View full text |Cite
|
Sign up to set email alerts
|

First report of L1014F-kdr mutation in Culex pipiens complex from Morocco

Abstract: BackgroundMosquitoes of the Culex pipiens complex, competent vectors for West Nile virus (WNV) and Rift Valley fever virus (RVFV) are widely targeted by insecticide treatments. The intensive application of chemical insecticides led to the development of resistance in many insects including Culex pipiens mosquitoes. The absence of data on resistance mechanisms in Morocco allow us to assess the levels of lambda-cyhalothrin resistance and the frequency of the mutated gene L1014F kdr in different forms of Cx. pipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
2
23
3
1
Order By: Relevance
“…This study showed that the distribution of the L1014F kdr mutation is widespread, particularly in the pipiens form and hybrids. Our previous report has documented the presence of a 1014 L/1014F genotype in three regions of Morocco including Tangier, Casablanca and Marrakech [ 22 ]. These results confirmed that the frequencies of 1014 L/1014F genotype are variable depending on the area [ 31 , 32 ], and the L1014F kdr mutation is widespread in different sites of Morocco from the North (Tangier) to Marrakech in the South.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the distribution of the L1014F kdr mutation is widespread, particularly in the pipiens form and hybrids. Our previous report has documented the presence of a 1014 L/1014F genotype in three regions of Morocco including Tangier, Casablanca and Marrakech [ 22 ]. These results confirmed that the frequencies of 1014 L/1014F genotype are variable depending on the area [ 31 , 32 ], and the L1014F kdr mutation is widespread in different sites of Morocco from the North (Tangier) to Marrakech in the South.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens larvae to temephos [ 20 , 21 ] and recently, our team described the presence of kdr mutation in different forms of Cx. pipiens [ 22 ]. This study aimed to evaluate the insecticide susceptibility status and investigate the target site mutation frequencies (G119S and L1014F) in Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Le paludisme est la maladie parasitaire la plus répandue dans le monde (Bkhache, 2016 ;Labbé et al, 2017). Cette maladie endémique potentiellement mortelle, due à des parasites Hemococcidae du genre Plasmodium (P.), est transmise à l'homme par des piqûres des femelles d'Anopheles (An.)…”
Section: Introductionunclassified
“…Specific mutations in the gene coding for the voltage-gated sodium channel decrease neuronal sensitivity to pyrethroids, resulting in insecticide resistance [ 13 ]. This form of resistance, known as knockdown resistance ( kdr ), is one of the most common mechanisms of resistance among insects, including anophelines [ 14 16 ]. Two point mutations occurring in codon 1014 of the voltage-gated para sodium channel gene have been associated with insecticide resistance in Anopheles gambiae ( s.l. )…”
Section: Introductionmentioning
confidence: 99%